2019
DOI: 10.1002/ange.201906214
|View full text |Cite
|
Sign up to set email alerts
|

2D Crystal Engineering of Nanosheets Assembled from Helical Peptide Building Blocks

Abstract: The successful integration of 2D nanomaterials into functional devices hinges on developing fabrication methods that afford hierarchicalcontrol across length scales of the entire assembly.W ed emonstrate structural control over ac lass of crystalline 2D nanosheets assembled from collagen triple helices.Bylengthening the triple helix unit through sequential additions of Pro-Hyp-Gly triads,w ea chieved sub-angstrom tuning over the 2D lattice.T hese subtle changes influence the overall nanosheet size, which can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…182 Crystallizable collagen triple helices based on collagenmimetic peptides have been shown to undergo seeded growth to form size-tunable 2D nanosheets (see Figure 4b). 183 Seeded heteroepitaxial growth was also demonstrated with this system to produce segmented 2D core-shell structures. The majority of early living CDSA experiments involved long periods of time (typically 24 h) in order to achieve complete unimer consumption.…”
Section: The Living Cdsa Seeded Growth Methodsmentioning
confidence: 95%
See 1 more Smart Citation
“…182 Crystallizable collagen triple helices based on collagenmimetic peptides have been shown to undergo seeded growth to form size-tunable 2D nanosheets (see Figure 4b). 183 Seeded heteroepitaxial growth was also demonstrated with this system to produce segmented 2D core-shell structures. The majority of early living CDSA experiments involved long periods of time (typically 24 h) in order to achieve complete unimer consumption.…”
Section: The Living Cdsa Seeded Growth Methodsmentioning
confidence: 95%
“…152,208,[212][213][214][215][216][217][218] Future challenges include the further development of heteroepitaxial growth processes, in which crystalline core-forming blocks with different chemistries but similar lattice parameters will grow from a seed. To date, successful examples are limited, 39,154,183,219 but further generalization will offer opportunities to access structures with of desirable combinations of properties, including heterojunctions with applications in optoelectronics. The ability of uniform 1D and 2D micellar nanoparticles to form ordered liquid crystalline phases in solution and to respond to stimuli are also areas worthy of further exploration.…”
Section: Discussionmentioning
confidence: 99%
“…The unique chemical reactivity and physical properties of two-dimensional (2D) molecular allotropes has opened new and exciting opportunities in chemistry, nanotechnology, and materials science. , To this end, a myriad of inorganic and organic bottom-up approaches toward 2D covalent and supramolecular materials have been developed over the past decade . Directed DNA and protein folding at the nanoscale have allowed the preparation of 2D biocompatible materials. ,− In particular, peptide-based scaffolds that undergo 2D self-assembly , include peptides, − proteins, ,, peptoids, , and derivatives thereof, , which have found applications in sensing, , catalysis, and molecular biology . However, despite remarkable progress in supramolecular systems, a synthetic small molecule with different preprogrammed levels of hierarchical self-assembly and adaptive behavior has remained elusive.…”
Section: Introductionmentioning
confidence: 99%
“…Our experimental observations reveal that different kinds of hydrophilic interactions, no matter if ionic ( B 4 A , B 4 N , and B 4 POM ) or neutral ( B 4 D ), can help to prevent 2D crystals of the SCGMs from stacking along the surface normal direction. In the literature, ionic groups are usually introduced in the building blocks to provide repulsive electrostatic interactions for the self-assembled 2D nanostructures. − Here, we showed that ionic repulsion is not a necessary factor to stabilize 2D crystals of SCGMs. We propose that, as long as the enthalpic interactions between the hydrophilic components and solvents are strong enough to overcome that among hydrophilic components themselves, the solvation effect should be enough to inhibit the stacking along the third direction.…”
Section: Resultsmentioning
confidence: 75%